Non‐isolated multiple‐input boost converter for energy harvesting. Issue 16 (1st August 2017) - Colalongo, L.; Dotti, D.; Richelli, A.; Kovács‐Vajna, Zs. M.
Abstract : In this Letter, a new dual/multiple‐input non‐isolated boost converter is proposed. It provides a positive boosted output voltage without any additional transformer. It is suitable to interface sources of different current–voltage characteristics to a common load, with a simple topology and a low part count. The topology and the behaviour are similar to the single‐input boost converter; hence, the control strategy can be accomplished easily. It can be used in low‐voltage energy harvesting applications to collect energy from multiple sources. Simulations and experimental results are presented to demonstrate the effectiveness of the proposed topology.